1967
DOI: 10.1136/jnnp.30.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of multiple sclerosis in Israel: Part III Multiple sclerosis and socio-economic status

Abstract: The frequency of multiple sclerosis increases with latitude both in the northern and southern hemisphere (Dean, 1949;Kurland, Mulder, and Westlund, 1955;Acheson, Bachrach, and Wright, 1960;Sutherland, Tyrer, and Eadie, 1962). This peculiar distribution suggests that an environmental factor (or factors) whose distribution is also correlated with latitude plays a role in the aetiology of the disease. The nature of the environmental factor remains obscure, although a wide variety of factors, including climatic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1969
1969
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Twelve case–control studies and one cohort study did not find an association between SES and MS risk. The cohort study included all incident cases in Denmark over a 26‐year period and benefited from contemporaneous collection of data on childhood SES.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Twelve case–control studies and one cohort study did not find an association between SES and MS risk. The cohort study included all incident cases in Denmark over a 26‐year period and benefited from contemporaneous collection of data on childhood SES.…”
Section: Resultsmentioning
confidence: 92%
“…Despite this strength, many of the case–control studies suffered from small sample sizes, resulting in wide confidence intervals which included large effect sizes along with the null value . Additionally, many studies used prevalent rather than incident cases . This increases the risk of bias as recall of events or exposures in the pre‐morbid state might be distorted by the length of time since diagnosis and the effect of disease .…”
Section: Resultsmentioning
confidence: 99%
“…Most retrospective case-control comparisons by a number of workers have revealed no significant associations, other than the accepted geographic variations (11,12,20,115,120,206,220,222,(224)(225)(226)282). Poskanzer (220,222) reported that patients had had a tonsillectomy in more instances than had either their spouses or their nearest siblings; however, these results have not been replicated.…”
Section: Personal Characteristicsmentioning
confidence: 97%
“…Poskanzer (220,222) reported that patients had had a tonsillectomy in more instances than had either their spouses or their nearest siblings; however, these results have not been replicated. In the Israeli studies, there were possible inverse relationships with indices of poor sanitation and a direct relationship to some features of urbanization (12,20). Reports implicating canine distemper or dog exposure have been published, but to date these also remain unverified (see reference 151 for information up to 1983; later data do not seem to alter this conclusion).…”
Section: Personal Characteristicsmentioning
confidence: 99%
“…Var ious approaches have been used to settle this The investigation of urban or rural origin of patients revealed conflicting results [1][2][3][4]. Evaluation of the occupational pattern of patients in comparison with the general pop ulation [5][6][7] or with control groups [8] showed either no, or no consistent, devia tion. When the time course of MS incidence was followed in defined regions over several years or decades during which industrializa tion took place, some authors found a fairly constant rate [9,10] whereas a considerable 1 Supported by the Hertie Foundation.…”
Section: Introductionmentioning
confidence: 99%